An analysis on the issues of the rights of spouses in the Islamic family law in Malaysia - Abu Bakar, Md Zawawi; Wan Abdullah, Wan Abd Rahman Khudzri (2011)
This paper intends to analyze problems regarding mutual rights of Muslims married couple in Malaysia.It has drawn the attention of many researchers to carry out studies on this issue since there have been accusations and complaints on the implementation of the Islamic Family Law (IFL) by the Syariah Court, which is said to have discriminated the wife/women of their rights.The qualitative approach research employed interviews and content analysis as method of study on the Islamic Family Law as well as on the documented cases.The results of the research showed that among the most disputable cases were matters related to polygamy, fasakh, jointly acquired property and children custodian.Conversely, all data were analyzed by using the qualitative data analysis, concluded that the Islamic Family Law in Malaysia has infact implemented the concept of equality.